(untitled) (GIST – Education and Learning Research Journal, 2021)
The present study aimed at investigating the effects of scaffolding strategies using input and output-oriented tasks on Iranian EFL learners’ receptive and productive knowledge of lexical collocations. For this purpose, 540 adult intermediate-level EFL learners- both male and female- were selected and divided into six experimental groups; three input-oriented and three output-oriented tasks. Each experimental group received treatment under one of the three scaffolding strategies of direct corrective feedback, cooperative group technique, and visual cues. After the treatment period, a 40-item multiple-choice test and a 40-item fill-in-the-blanks test were administered to assess the participants’ receptive and productive collocations knowledge. To analyze the data, two separate two-way ANOVA procedures were used. The results indicated that visual cues were the most effective scaffolding strategy in teaching lexical collocations. Moreover, the cooperative group technique had a significant positive impact on learning collocations compared to direct corrective feedback. The results also showed that the participants in the output-oriented tasks group significantly outperformed those in the input-oriented tasks group. These findings can have practical implications for language learners, teachers, and materials developers, and theoretical implications for researchers.